Early impairment of coronary microvascular perfusion capacity in rats on a high fat diet. Issue 1 (December 2015) - Haare, Judith; Kooi, M.; Vink, Hans; Post, Mark; Teeffelen, Jurgen; Slenter, Jos; Munts, Chantal; Cobelens, Hanneke; Strijkers, Gustav; Koehn, Dennis; Bilsen, Marc
Abstract Background It remains to be established if, and to what extent, the coronary microcirculation becomes compromised during the development of obesity and insulin resistance. Recent studies suggest that changes in endothelial glycocalyx properties contribute to microvascular dysfunction under (pre-)diabetic conditions. Accordingly, early effects of diet-induced obesity on myocardial perfusion and function were studied in rats under baseline and hyperaemic conditions. Methods Rats were fed a high fat diet (HFD) for 6 weeks and myocardial microvascular perfusion was determined using first-pass perfusion MRI before and after adenosine infusion. The effect of HFD on microcirculatory properties was also assessed by sidestream darkfield (SDF) imaging of the gastrocnemius muscle. Results HFD-fed rats developed central obesity and insulin sensitivity was reduced as evidenced by the marked reduction in insulin-induced phosphorylation of Akt in both cardiac and gastrocnemius muscle. Early diet-induced obesity did not lead to hypertension or cardiac hypertrophic remodeling. In chow-fed, control rats a robust increase in cardiac microvascular perfusion was observed upon adenosine infusion (+40 %; p < 0.05). In contrast, the adenosine response was abrogated in rats on a HFD (+8 %; N.S.). HFD neither resulted in rarefaction or loss of glycocalyx integrity in skeletal muscle, nor reduced staining intensity of the glycocalyx of cardiac capillaries. Conclusions Alterations in coronary microcirculatory function as assessed by first-pass perfusion MRI represent one of the earliest obesity-related cardiac adaptations that can be assessed non-invasively. In this early stage of insulin resistance, disturbances in glycocalyx barrier properties appeared not to contribute to the observed changes in coronary microvascular function.